Structural and species diversity on North and South slopes in coniferous-deciduous forests of the North-Western Caucasus - Shevchenko, Nikolaj; Geraskina, Anna (Ecological Questions, 2022)
The research was conducted in similar soil-orographic conditions of three widespread coniferous-deciduous forest types in the North-Western Caucasus: aspen-hornbeam, beech-fir-hornbeam, and fir-beech. The methods used included geobotanical, population-ontogenetic, and soil-zoological. It was found that the north and south slopes in all the studied forest types, in comparison with the flat areas, are characterised by significantly higher plant species richness. The efficiency of the renewal of arboral cenopopulations was much higher on the slopes, in comparison with the flat areas: the number of tree species (higher by 20–70%); density of tree species (higher by 50–100%); the number of cenopopulations of tree species with a complete ontogenetic spectrum was larger on the slopes, in comparison with the flat areas. A greater number of ecological groups of plants were described on the north and south slopes, in comparison with the flat areas. The proportion of boreal species was higher on the north slopes, in comparison with the south slopes, whereas the majority of meadow-forest edge species were the south slopes. The north and south slopes were characterised by the full functional diversity of soil invertebrates, whereas endemic and sub-endemic macrofauna also preserved. On the north slopes, we revealed a high biomass of large litter and soil saprophages, including species and groups actively participating in transformation of plant litter and soil formation. The south slopes showed high densities of phytophages and predators (among soil macrofauna), which regulate the diversity of other components of forest communities through biotic interactions. All the studied forest types on the north and south slopes exceeded the flat areas in terms of species diversity of plant communities, regeneration of tree species, ecological plant groups, endemic fauna of soil invertebrates, including soil formers. This confirms need to the protection of such territories to preserve and maintain the biological diversity of the coniferous-deciduous forests in the North-Western Caucasus.